Aplikasi Pupuk Organik Cair Tomat dan Cendawan Mikoriza Arbuskula Pada Tahap Aklimatisasi Terhadap Produksi Tanaman Kentang (Solanum tuberosum L.) Varietas Granola di Tongkoh - Lisdayani, Lisdayani; Samah, Eri; Pamungkas, Agung Gusti (JURNAL AGROPLASMA, 2025)
Potatoes have high nutritional value, making this plant widely cultivated in various regions in Indonesia. In Indonesia, this potato commodity has a fairly important role to be used as a material for household business industries, often also used as processed foods and made into flour and chips in large industries. The purpose of the study was to determine the effect of providing liquid organic fertilizer from tomatoes and the provision of arbuscular mycorrhizal fungi on potato plants at the acclimatization stage. This study was conducted in the IP2TP greenhouse (Berastagi Agricultural Technology Research and Assessment Installation), in Tongkoh, Dolat Rayat District with an altitude of ± 1340 meters above sea level. The research period began in September to December 2023. The results of the study showed that the provision of Liquid Organic Fertilizer (POC) Tomato (T) had a significant effect on tuber diameter and no significant effect on the number of tubers and tuber diameter. The best treatment was T2 (200 ml/L of organic fertilizer), and the application of Arbuscular Mycorrhizal Fungi (AMF) (C) had no significant effect on tuber number and diameter, with the best treatment being C2 (10 g AMF/plant). Keywords: potato, AMF, tomato organic fertilizer